PENINGKATAN SIFAT MEKANIK MATERIAL RING PISTON NON ORIGINAL MESIN PADA MESIN DIESEL MITSUBISHI-MAN 18 V52/55A PLTD TELLO UNIT 1 - Win Alfalah (Sekolah Tinggi Teknik - PLN, 2018)
The purpose of this study, to determine the characteristics of piston ring material compression Tello diesel engine. Non original (NOM) diesel engine piston rings are heat treated with a holding time of 1.2 and 3 hours then hardness test, metallograhic test and chemical composition test.From the results of these test, compared with the results of the original diesel engine piston ring (OM) and piston ring (NOM) tests which were not subjected to heat treatment. The results obtained show a significant different between the OM piston ring and NOM piston ring with a hold time of 1. 2 and 3 hours especially in the hardness value. For OM and NOM piston ring elements 0f 77.5% and 89.2%, while carbon elements have the same value of >4 %. Whereas the results of microstructure testing show that the shape of graphite from several materials is different, both in form and size of graphite. For the hardness of the NOM piston ring with a hold tome of 3 hours the hardness value of 301 HV approaches the OM piston ring of 309 HV.